Integrating Culture Awareness and Formalisation in Software Process Assessment and Improvement for Very Small Entities (VSEs) - Nonoyama, Tatsuya; Kabaale, Edward; Wen, Lian; Tuffley, David; Wang, Zhe (Springer, Cham, 2018)
Software process assessment and process improvement are fundamentally essential if software companies are to improve their development processes and perform at best practice level. However, established software process assessment models (PAMs) like SPICE or CMMI are scaled to be applicable to Small and Medium Enterprises (SMEs) all the way up to very large companies. So far, there is no mature PAM applicable to Very Small Entities (VSEs), which are usually defined as companies with 25 or less employees. As the majority of software companies are classified as VSEs, the lack of a mature PAM is a glaring omission in the Software Engineering domain in need of rectification. A major challenge with producing a VSE-appropriate PAM is the cultural diversity of VSEs. It is not amenable to a one size fits all solution suitable for all VSEs. Another challenge is the high human resource cost of a SPICE or CMMI process assessment. It is often cost-prohibitive for VSEs. This paper therefore proposes a model to meet the need; the Culture Impact on Software Assessment (CISA). CISA facilitates the development of PAMs that are both lightweight, making them easy and cheap to apply, while also being highly relevant to individual VSE, thereby significantly increasing the efficiency of PAMs. Additionally, this paper introduces a formal specification (ontology) of CISA to enable future development of software process semi-automatic assessment tools that will greatly reduce the cost for software process assessment for VSEs.
Keywords: Process assessment model; Process improvement; Ontology; Culture evaluation